The Role of Social Crowdsourcing in Mobile Tourism - TYAGI, DR. PANKAJ KUMAR; SINGH, AJIT KUMAR; SINGH, DR. VIKRAMJIT; TYAGI, PRIYANKA (The journal of contemporary issues in business and government, 2021)
Social networks and online communities are increasingly becoming a big player in the field of tourism marketing. Consumer behavior is increasingly more influenced by the information exchanged on these communities. Being a community of individuals linked together based on different criteria such as geographic positioning, centers of interest and needs that may be close or similar, social media users can exchange views, opinions, experiences, their recommendations or their disclaimers. This allows to consider the social networks or online communities as a source of information, procurement and learning The purpose of this study is to investigate the behavior of tourists towards using a mobile application which is based on the sharing of feedback and opinions of other fellow travelers. We have used a predesigned questionnaire for conducting the survey. The questionnaire was designed to analyze a user’s behavior towards the use of mobile technology during a trip and the impact of their reviews on others.